19th Annual Fresno County Legal Secretaries Association Annual Bosses' Night Honoring Gaspar Magarian - Watkins, Howard::::::::: (1987)
California Legal Secretaries, Inc. President Joyce Seymour, Fresno County Legal ServicesA President Mildred Christian; 1987 Boss of the Year Gaspar Magarian; 1987 Legal Secretary of the Year Joan Kleinsteuber, and Emcee Justice Hollis Best Most wearing eyeglasses